Walking Toward Green Man: Encounters with the Sacred Masculine. (3rd July 2017) - Smith, Drew
Abstract : My intention in taking a medicine walk was to finally encounter Green Man, the elusive and ancient archetypal figure representing the masculine spirit within nature. Symbolized by the face in the tree, he is the uniting essence joining the archetypal Sky Father to Earth Mother, bringing polarized (and polarizing) energies into alignment and harmony. He is a central symbol often hidden within most major myths and religions, unidentifiable unless you know where and how to look. Today Green Man takes form as a prophetic voice for the planet, challenging the population to return to its roots, dig deep, and ground itself once again for the sake of future generations—if only we would listen. This medicine walk was a chance to hear what he had to say, but the daylong journey felt rather lackluster and uneventful, and it seemed as if Green Man had eluded me yet again. However, much post-walk introspection and mirroring with my companions revealed that he not only made contact with me, but that he has been walking with me for years, whispering in my ear, and I simply did not acknowledge him. This is the story of a seemingly banal medicine walk that ended up revealing a sacred and abiding relationship with Green Man, who then initiated me into the new realm of Father Earth.